UPAYA MENINGKATKAN PENGEMBANGAN BAHASA ANAK MELALUI LAYAR PROYEKTOR - Eti Pratiwi; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to improve language development through the media of group B projector screens at Kusuma Mekar I Kindergarten. Language development in this study is the child's ability to understand language, express language, and literacy. This research is a class action research (classroom action research). The subjects of this study were 19 students in group B, consisting of 8 boys and 11 girls. Data collection techniques are carried out by means of observation and documentation. The research instrument is an observation guide. The data analysis used in this study is descriptive qualitative and quantitative descriptive with percentages. The results showed that language development in group B children at Kusuma Mekar I Kindergarten could be improved through the media of a projector screen. This is evidenced by the results achieved in cycle 1, language skills with an average BB reaching 2 children (10%), MB reaching an average of 11 children (58%), BSH reaching an average of 3 children (17%) ), and language skills with average BSB achievements reached 3 children (17%). In cycle 2, language skills with BB achieved an average of 0 children (0%), MB averaged 0 children (0%), BSH averaged 3 children (16%), and language skills with achievements BSB averaged 16 children (84%). Effective steps in this study in an effort to improve language development through a projector screen for group B children of Kusuma Mekar I Kindergarten, namely 1) The teacher changes the implementation technique classically divided into three playing groups, 2) To spur enthusiasm and self-confidence of children in express opinions, the researchers provide rewards in the form of gifts for children who are able to play educational games well, 3) educational game games are made with variations, so it is hoped that children will be more interested.